ESTRATÉGIAS ARGUMENTATIVAS EM AVALIAÇÕES NO ENSINO SUPERIOR - Mariano, Márcia Regina Curado Pereira (Intercâmbio, 2010)
The purpose of this work is to analyze the answers elaborated by students of the first year of the language and literature course in written tests, and to observe the main argumentative strategies used to persuade the teacher.